Protótipo de panela-dessalinizador circular para fogão solar com aquecimento indireto - Herculano, Rafael Teixeira (2015)
Extensive research and development activities have been conducted to explore opportunities for sustainable and viable methods of producing potable water using solar energy. This project included a new configuration for the solar cooker with indirect heating, which also operates as a desalination unit. The objective was to develop a new cooking pan which could be coupled with a three-stage desalination tower. Thus, the pan could be used for cooking or as the storage tank of the desalination tower. This new pan was installed in a solar cooker with indirect heating and the complete system was tested under field conditions. The sealing was improved, and the system produced more than 5.7L, with electrical conductivity lower than 10µS/cm, COP, 1.77 and GOR, 0,35, values consistent with the literature and above the values obtained with the original pan